Microplate assay for endo-polygalacturonase activity determination based on ruthenium red method - Ortiz, Gastón Ezequiel (2014)
Endo-polygalacturonase (endo-PGase) activity determinations generally rely on viscosity changes or reducing sugar ends produced by this activity over polygalacturonic acid. Torres and coworkers [Enzyme Microb. Technol. 48 (2011) 123–128] showed that ruthenium red (RR) is useful for endo-PGase determination. In this article, we present a high-throughput liquid-based endo-PGase assay based on the RR method and compare it with the viscosity determination method. The reduced assay uses a small volume of enzyme solution, 40 μg of polygalacturonic acid, and 45 μg of RR for each sample determination. Furthermore, we obtained an interconversion factor for RR and viscosity activities.